Biomaterial-based circular RNA therapeutic strategy for repairing intervertebral disc degeneration - Hongze Chang; Feng Cai; Xiaohu Li; Ang Li; Yan Zhang; Xiaolong Yang; Xiaodong Liu (Biomedical Technology)
Intervertebral disc degeneration (IDD) is the leading cause of low-back pain, which brings huge threaten to patients' life and workability. However, IDD's pathophysiology is still a puzzle, thus conventional conservative therapy leads to little success. Among all advanced therapies, the rising gene therapy might be the most promising, which combats diseases by the long-term expression of therapeutic proteins, silencing pathological genes, or editing genes. Since circular RNA (circRNA) is a critical regulator in nucleus pulposus cells' proliferation, apoptosis and extracellular matrix metabolism, making it an important research object for IDD repair. To target the pathogenic gene, silencing gene medicines carried by biomaterials have produced interesting breakthroughs in the safe, manageable, and effective administration. In this review, we took an insight into circRNA-related properties and biological processes, so as to inspire IDD treatment. At the same time, we focused on the circRNA related therapies for the treatment of IDDs by using biomaterial-based delivery systems. To note, we also discussed the perspectives of biomaterial-delivered gene therapies as effective means from the frontier needs in biomedicines, to facilitate the rapid development of biomaterial-based delivery systems.